RESEARCH ON THE SUBFAMILY CHRYSIDINAE (HYMENOPTERA: CHRYSIDIDAE) FAUNA OF TURKEY WITH DISTRIBUTIONAL EVALUATION (Acta Entomologica Serbica, 2019)
The present study is based on chrysidid samples in the subfamily Chrysidinae collected from various parts of Turkey since the 1970s. A total of 90 species and subspecies are recognized in seven genera: Chrysidea (1), Chrysis (70), Chrysura (13), Pseudochrysis (2), Spinolia (2), Spintharina (1), and Euchroeus (1). Of these, Chrysis verae Semenov 1967 is new for the Turkish fauna. Moreover, Chrysis cingulicornis Förster 1853, Ch. cylindrica Eversmann 1857, Ch. decora Mocsáry 1889, Ch. lepida Mocsáry1889, Ch. marani centropunctata Linsenmaier 1968, Ch. viridissima fasciolata Klug 1845, Chrysura barbatula Linsenmaier 1968, and Pseudospinolia neglectoides (Linsenmaier 1959) are recorded for the first time in the eastern Anatolian region. Those of Chrysis confluens (Dahlbom 1845) and Euchroeus purpuratus consularis Buysson 1896 are recorded from central and eastern Anatolia, Chrysis bytinskii Linsenmaier 1959 from the Mediterranean region, Chrysis krueperi Mocsáry 1897 from the Marmara region, Ch. marginata Mocsáry 1889 from central Anatolia and Mediterranean regions, Ch. lateralis Dahlbom, 1845 from central Anatolia, Chrysura varicornis (Spinola 1838) from the southeastern Anatolian region. New distributional data of most of the taxa are evaluated. The species show different distribution patterns; most of them have been rarely recorded, the rest of them are moderately and frequently recorded. Certain species are recorded from one or two provinces, even with a single sample. For instance, Chrysis aeraria (Mocsáry, 1914), Ch. jucunda Mocsáry, 1889 and Ch. viridissima fasciolata Klug, 1845 are known from one province each. They could be classified as endangered species and should be added to the IUCN red list.